1995
DOI: 10.1111/j.1475-6803.1995.tb00560.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term and Short‐term Causal Relations Between Dividends and Stock Prices: A Test of Lintner's Dividend Model and the Present Value Model of Stock Prices

Abstract: In this paper we test the joint implications for the intertemporal behavior of stock prices and dividends expressed in the Lintner dividend model and the present value model of stock prices. We use macro data corresponding to quarterly S&P 500 index prices and dividends for January 193O-December 1990. The methodology used is the error correction model (ECM), which allows testing for long-term and short-term relations between the two variables. Results from the ECM indicate that a long-term equilibrium relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 14 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Besides the present value model of stock price, the Lintner (1956) dividend model has been used by Sung and Urrutia (1995) to derive models of causality from stock prices to dividends and vice versa. They state that, as per the Lintner's model, current dividend is determined by current target dividend and past dividends, and that, as per the present value model, current and past stock prices are determined by current target dividend and past dividends.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides the present value model of stock price, the Lintner (1956) dividend model has been used by Sung and Urrutia (1995) to derive models of causality from stock prices to dividends and vice versa. They state that, as per the Lintner's model, current dividend is determined by current target dividend and past dividends, and that, as per the present value model, current and past stock prices are determined by current target dividend and past dividends.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these relations, they derived model of causality from stock prices to dividends and concluded that current and past stock prices affect current dividends. Sung and Urrutia (1995) further state that, as per the present value model, the current stock price is determined by future dividends, and that, as per the Lintner's model, future dividends are determined by current and past dividends. From this, they derived model of causality from dividends to stock prices and thereby concluded that current and past dividends affect current stock prices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they mentioned the existence of a unique cointegration relationship between stock prices and dividends when retained earnings were included in the equation. Sung and Urrutia (1995) also explored the existence of bi-directional causality between stock price and dividend. They observed cointegration between stock price and dividends and significant bi-directional causality between both the variables.…”
Section: The Present Value Model: Theory and Empirical Literaturementioning
confidence: 99%